2019
DOI: 10.1016/j.carbon.2018.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced resolution of ultra micropore size determination of biochars and activated carbons by dual gas analysis using N2 and CO2 with 2D-NLDFT adsorption models

Abstract: In this study, biochars obtained by either direct carbonization or hydrothermal treatment of corn stems were used as precursors of two series of activated carbons (ACs). The pore size distributions (PSDs) of biochars and ACs were evaluated from N 2 and CO 2 adsorption isotherms using models based on the two-dimensional version of the non-local density functional theory (2D-NLDFT). We showed that more detailed carbon PSDs might be obtained from simultaneous (dual) gas analysis of both N 2 and CO 2 isotherms tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 41 publications
3
78
1
Order By: Relevance
“…The char derived from corn stigmata was labeled C-CS, and its two activated carbon derivatives were labeled C-CS-0.5 and C-CS-1.0, where the number in the sample label represents the time of activation in hours. Preparation and properties of the samples used in this work were described earlier for the PET series [16,23] and the CS series [24]. In addition to the porous carbons, a sample carbon black BP 280 (Cabot) was used to obtain H 2 adsorption reference data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The char derived from corn stigmata was labeled C-CS, and its two activated carbon derivatives were labeled C-CS-0.5 and C-CS-1.0, where the number in the sample label represents the time of activation in hours. Preparation and properties of the samples used in this work were described earlier for the PET series [16,23] and the CS series [24]. In addition to the porous carbons, a sample carbon black BP 280 (Cabot) was used to obtain H 2 adsorption reference data.…”
Section: Methodsmentioning
confidence: 99%
“…The limited sensitivity to larger pore sizes of CO 2 and H 2 implies that to calculate the carbon PSD in a full range of micro and mesopores, it is necessary to use an additional adsorbate that will condense in the larger pores. The concept of using two adsorbates that are sensitive to different pore sizes was implemented for CO 2 and N 2 in the dual gas analysis method [16,24].…”
Section: Two-dimensional Slit Pore Model With Quantum Correctionsmentioning
confidence: 99%
“…2(a). The results indicated that the HS-2D NLDFT model could detect the existence of a peak at about 0.4 nm, but the slit-NLDFT model only could probe down to 0.6 nm; (23) thus, the HS-2D-NLDFT model was subsequently used. The PSD patterns of carbonized samples [ Fig.…”
Section: Surface Featuresmentioning
confidence: 99%
“…The corresponding results are given in Table 2. The pore size distributions (PSDs) were also obtained by applying the 2D-NLDFT-HS method, which provides more accurate results by combining N 2 and CO 2 adsorption data simultaneously [50][51]. By integration of the PSDs over the entire range of pore sizes [52] (not shown), the S NLDFT surface areas and the total pore volumes could be calculated and are also presented in Table 2.…”
Section: Physical Properties Of the Carbonized 3d-printed Lignin-go Smentioning
confidence: 99%